REFORMASI BIROKRASI DINAS TENAGA KERJA KOTA DEPOK DALAM UPAYA PENANGGULANGAN PENGANGGURAN - Wahid Aldi Nugroho (2023)
This study examines the bureaucratic reform of the Depok City Manpower Office in tackling unemployment in Depok City. The problem of unemployment in Depok City is an important problem because the Open Unemployment Rate in Depok City is quite high. Apart from that, the community's competitiveness in absorbing labor into companies is still low, while the workforce in Depok City is high, which is not aligned with employment so that the unemployment rate increases year on year. This happened because of internal bureaucratic obstacles in the employment agency of the Depok City Manpower Office itself such as the absence of the UPTD BLK to be able to provide job training, the performance ofthe Depok City Manpower Office which received a "C" or "Not Good" category and so on. Researchers used descriptive qualitative research methods using primary data sources such as in-depth interviews, observation and documentation. And secondary data sources such as Depok City Manpower Office documents such as Strategic Plans, Work Plans and so on. The results of this study indicate that there is an imbalance that occurs as a result of an unbalanced internal and external bureaucracy that hinders bureaucratic reform. This is because the internal bureaucracy of the Depok City Manpower Office is still thick with bureaucratic pathology in public services for dealing with unemployment while externally the Depok City Manpower Office bureaucracy can provide useful services to affected communities. Keywords: Bureaucratic Reform, Bureaucratic Pathology, Public Services for Overcoming Unemployment